Technology use in long-term care during the COVID-19 pandemic: A qualitative study of paid employees’ experiences in Western Canada - Hui-Jun Chew; Shannon Freeman; Piper Jackson; Dawn Hemingway; Tammy Klassen-Ross; Melinda Martin-Khan; Davina Banner (Digital Health)
Background During the COVID-19 pandemic, governments across the world implemented processes and policies to limit the spread of COVID-19, especially in long-term care (LTC) homes. This led to changes in technology use for persons living in LTC homes, their families and friends, as well as the paid workforce dedicated to caring for them. Objective The study describes the role of technology and its impact on the experiences of LTC staff working in northern and rural areas in Western Canada during COVID-19. Methods A secondary analysis of semi-structured interviews with 52 LTC staff was conducted. Qualitative data was analysed thematically using Braun and Clarke's thematic analysis approach. Results Analysis of the study data revealed that new and innovative uses of technology emerged in the LTC setting during COVID-19, including technologies to support communication and collaboration with medical and health care professionals external to the LTC homes. Video-conferencing technology were rapidly implemented to facilitate virtual visits for LTC residents to connect to their families, further new streaming services were introduced to support recreational activities, including live music and spiritual services. LTC residents required significant support from staff to participate in virtual activities. Inadequate Internet infrastructure and scheduling difficulties in the context of severe staff shortages created challenges in technology adoption. Conclusions This research provides insight into how technology can support LTC teams in northern and rural communities, as well as supports needed for LTC residents and staff to integrate technology effectively. The study informs actionable insights for those working in rural LTC settings.